1995
DOI: 10.1038/bjc.1995.82
|View full text |Cite
|
Sign up to set email alerts
|

Cancer incidence in Asian migrants to New South Wales, Australia

Abstract: Cancer incidence during 1972-90 in Asian migrants to New South Wales, Australia, is described. Overall cancer incidence was lower than in the Australia born in most migrant groups, and this reached significance in migrants born in China/Taiwan, the Philippines, Vietnam and India/Sri Lanka, and in male migrants born in Indonesia. For the majority of cancers, rates were more similar to those in the Australia born than to those in the countries of birth. For cancers of the breast, colorectum and prostate, rates w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
76
0
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(83 citation statements)
references
References 26 publications
5
76
0
2
Order By: Relevance
“…An excess risk was seen among Vietnamese migrants to the USA (Ross et al, 1991) and Australia (Grulich et al, 1995) but migrants to England and Wales, who were probably from the north rather than the south of Vietnam, showed a low incidence and mortality from cervical cancer (Swerdlow, 1991). That the excess remained 30 years after migration might be explained by persistence of the relevant risk factor or by the possibility that these migrant women have not taken advantage of the availability of screening by Papanicolaou smear for pre-cancerous lesions or of treatment for cancers at an early stage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An excess risk was seen among Vietnamese migrants to the USA (Ross et al, 1991) and Australia (Grulich et al, 1995) but migrants to England and Wales, who were probably from the north rather than the south of Vietnam, showed a low incidence and mortality from cervical cancer (Swerdlow, 1991). That the excess remained 30 years after migration might be explained by persistence of the relevant risk factor or by the possibility that these migrant women have not taken advantage of the availability of screening by Papanicolaou smear for pre-cancerous lesions or of treatment for cancers at an early stage.…”
Section: Discussionmentioning
confidence: 99%
“…The countries and numbers of cancer deaths contributing to each region within Asia were: East Asia (1301) comprising China (1054), Hong Kong (149), Japan (30), Korea (62) and Taiwan (6); and Southeast Asia (879) comprising Myanmar (Burma; 33), Cambodia (44), Indonesia (164), Laos (39), Malaysia (119), Philippines (185), Singapore (52), Thailand (7) and Vietnam (236). As the pattern of cancer incidence was similar for migrants from East and Southeast Asia (Grulich et al, 1995), the main analyses were carried out for these groups combined.…”
Section: Methodsmentioning
confidence: 99%
“…Familial clustering has also been frequently reported . Furthermore, the risk of developing NPC in migrants originating from highincidence areas does not diminish (Li et al, 1983;Grulich et al, 1995). Linkage or association studies have demonstrated a correlation between the HLA haplotype and NPC susceptibility (Lu et al, 1990(Lu et al, , 2003.…”
Section: Genetic Susceptibilitymentioning
confidence: 99%
“…We used the structure of these questionnaires to create the general framework for our survey. We divided our survey into six sections, in order to determine: Participant demographic and qualifications (1); Knowledge of NPC in the areas of epidemiology (2), aetiology (3), symptoms (4), and management (5); and Source of knowledge and desire for further education (6). Questions consisted of multi-tick boxes, close-ended questions, and sliding scales.…”
Section: Survey Developmentmentioning
confidence: 99%
“…However, a study conducted between 1972 and 1990, showed the incidence of NPC in Vietnamese and Chinese migrants living in NSW to be 12.3 and 17 per 100000, respectively [6]. The area of Greater Western Sydney (GWS) is a highly multicultural region with a large number of Southeast Asian migrants [7,8].…”
Section: Introductionmentioning
confidence: 99%